The Transfer of Arabic in the English Writings of Lebanese Students - Diab, Nuwar (The ESPecialist, 2012)
The purpose of this paper is to show through error analysis the interference of the mother-tongue, Arabic, in the English writings of Lebanese students, which leads to language transfer. To this end, I have collected 73 English essays written by Lebanese sophomore students studying at the American University of Beirut. Since my mother-tongue is also Arabic, the transfer errors made by these students were easily spotted upon examining their essays, thus simplifying the task of error analysis. What remained was a subclassification of these errors. It turned out that the transfer of Arabic linguistic structures influenced the English writings of Lebanese students on the grammatical, lexical, semantic and syntactic levels.